Multimedia archaeologies : Gabriele D'Annunzio, Belle Époque Paris, and the total artwork - Mirabile, Andrea, 1975- (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft ;, 2014)
Paris, 1910-1915. Artists, intellectuals, and international celebrities crowd the city as never before. Decadent dreams and avant-garde manifestos celebrate the marriage between art and life. Creative experiments and vital joy dance hand in hand-on the edge of the abyss of WWI. Gabriele D'Annunzio is one of the highly influential yet semi-forgotten protagonists of this season and an emblem of its contradictions. A child of the Decadence, but also a forerunner of Modernism, the Italian poet defies the barriers between art forms, languages, and aesthetic practices. Tellingly, some of the period'